Organização do trabalho pedagógico na escola da infância/creche e o uso dos registros audiovisuais: contribuições docentes - Curin, Jucelaine Domingues (2023)
This study contemplates the research carried out in the Postgraduate Program in Public Policies and Educational Management/Professional Master's Degree at the Federal University of Santa Maria, (UFSM), integrating Research Line 2 (LP2): Pedagogical Management and Educational Contexts. This research has the theme “Organization of pedagogical work and the use of audiovisual records in kindergarten/daycare centers”. The research on this topic represents the researcher's concerns about pedagogical work with babies and very young children and about the use of audiovisual records in the day-to-day life of the daycare center. The main objective is to understand the relationships between the organization of pedagogical work in daycare centers and the potential of audiovisual records. The research also addresses the term “emerging contexts”, as it is believed that these influence the ways of being and doing teaching (Bolzan, 2016). This research was carried out through narrative interviews and conversation circles as a methodological strategy for data production. The subjects participating in the study were six teachers who work in Early Childhood Education, the nursery stage of the Santa Maria Municipal Public Education Network. To support the investigation, the proposed methodology is based on qualitative research with a sociocultural narrative approach, based on the studies of Vigotski (2007), Freitas (2006), Bolzan (2001, 2002, 2006 and 2019), Clandinin and Connelly (2011) among others. The choice for this methodology emerges from the idea that the subject can express their way of thinking about what they develop and, consequently, be able to take into account their own experience and the experience of others in this relational process. In this direction, the research was carried out in two stages of investigation. Firstly, narrative interviews were carried out with the participants. The second stage included conversation circles. The interviews and conversation circles were based on guiding topics, which served as a starting point for establishing dialogue (Bolzan, 2019). From the interviews and conversation circles, we sought to discuss the pedagogical work in the daycare center and the use of audiovisual records. To reflect on the pedagogical work and monitor the development of babies and very young children, a script with guidelines/elements of observations for the kindergarten/daycare center based on audiovisual records was presented as a product. This script was constructed based on the triggering videos brought by the research participants as strategies for attentive listening and a sensitive and thinking look.